2021
DOI: 10.1186/s10194-021-01333-4
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological predictors of negative treatment outcome with Erenumab in chronic migraine: data from an open label long-term prospective study

Abstract: Background Monoclonal antibodies (mABs) targeting the calcitonin gene-related peptide (CGRP) pathway represent the first disease-specific preventive migraine therapy. Growing evidence suggests that they are effective in the preventive treatment of difficult-to-treat patients. In this study, we evaluated the psychological predictors of the outcome of treatment with the anti-CGRP monoclonal antibody erenumab in patients with chronic migraine (CM). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 65 publications
(69 reference statements)
2
32
1
Order By: Relevance
“…The presence of personality disorders belonging to Cluster C (e.g. obsessive–compulsive or dependent personality disorders), along with anxiety disorder, stressful events, and alexithymic traits seem to be determinants of erenumab treatment failure in individuals with CM [ 97 ].…”
Section: Psychological Factorsmentioning
confidence: 99%
“…The presence of personality disorders belonging to Cluster C (e.g. obsessive–compulsive or dependent personality disorders), along with anxiety disorder, stressful events, and alexithymic traits seem to be determinants of erenumab treatment failure in individuals with CM [ 97 ].…”
Section: Psychological Factorsmentioning
confidence: 99%
“…It can be speculated that, as previously demonstrated with Onabotulinumtoxin-A [ 48 ], the probability of being a responder to CGRP-targeting drugs may be higher in patients with increased peripheral trigeminal sensitization and CGRP production both leading to more intense headache attacks. Moreover, “catastrophizing” habits and abnormal cognitive and emotional approaches to the pain experience, are already known to be associated with poor response to preventive migraine treatments including CGRP-mAbs [ 37 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that responsiveness to antiCGRP mAbs could be related to several demographic and clinical features -including age, sex, body mass index, basal migraine frequency and disability, pain side and severity, allodynia, dopaminergic symptoms, response to triptans and psychiatric comorbidities and personality trait. The heterogeneity of these findings could depend on differences on populations studied, sample sizes, study designs and clinical endpoints investigated [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%